2003
DOI: 10.1159/000067032
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Pneumoperitoneum with Ozonized Oxygen as a Preventive in Lethal Polymicrobial Sepsis in Rats

Abstract: The aim of this study was to test whether repetitive pretreatments of rats with ozonized oxygen at relatively low gas volumes into the abdomen (20 ml per rat per day) have any beneficial or detrimental effects on the course of a polymicrobial-induced lethal peritonitis. Peritonitis was induced in a surgical or a nonsurgical model by usage of fecal material from the cecum. As the biological read out we used the mortality analysis. To include possible mechanisms by which ozone might influence the septic outcome,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 28 publications
0
33
1
Order By: Relevance
“…There are a few reports, both in animals and in humans, which demonstrate beneficial effects of ozone in peritonitis [9,15,16]. Our results disagree with these observations, since we found that ozone pre-treatment caused a trend to a reduced survival from 50 % to 35 %, which may be due to an exaggerated pro-inflammatory cytokine release, disturbing the delicate pro-and anti-inflammatory cytokine balance after infection [17].…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…There are a few reports, both in animals and in humans, which demonstrate beneficial effects of ozone in peritonitis [9,15,16]. Our results disagree with these observations, since we found that ozone pre-treatment caused a trend to a reduced survival from 50 % to 35 %, which may be due to an exaggerated pro-inflammatory cytokine release, disturbing the delicate pro-and anti-inflammatory cytokine balance after infection [17].…”
Section: Discussioncontrasting
confidence: 97%
“…Our senses model differs from others [9], since we administer an antibiotic prophylaxis in an equivalent human dosage. Others performed trials without antibiotic prophylaxis [18] or with a clinically unusual applications (e. g. intramuscular) [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schulz et al 14 found promising results on proving the efficacy of repetitive pre-treatment using intra-abdominal ozonized oxygen in reducing mortality in animals submitted to lethal polymicrobial peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of Bacillus subtilis spores with various oxidizing agents (including ozone) damages the inner membrane, making the spores more sensitive to subsequent thermal and osmotic stresses, with the increased rapid penetration of methylamine within the core [20]. The literature also confirms the synergic action of ozone with antibiotic therapy in vivo [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%